2004
DOI: 10.1097/01.ico.0000121701.74077.78
|View full text |Cite
|
Sign up to set email alerts
|

Pterygia With Deep Corneal Changes

Abstract: Long-standing nasal pterygia in elderly patients may rarely induce deep corneal changes at the level of the endothelium and Descemet membrane. Endothelial cell density may be lower in eyes with pterygia with deep corneal changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 6 publications
4
30
2
1
Order By: Relevance
“…10,16 In limited cases, the average central endothelial density of the involved cornea showed a significantly greater decrease than that of the unaffected eyes. 17 In this study, there was a significant association between a decrease in the ECD and an increase in the percentage of pterygium to cornea, and a logarithmic correlation was observed. A self-limiting phenomenon in the percentage of ECD loss resulting from pterygium extension may exist.…”
Section: Discussionmentioning
confidence: 71%
“…10,16 In limited cases, the average central endothelial density of the involved cornea showed a significantly greater decrease than that of the unaffected eyes. 17 In this study, there was a significant association between a decrease in the ECD and an increase in the percentage of pterygium to cornea, and a logarithmic correlation was observed. A self-limiting phenomenon in the percentage of ECD loss resulting from pterygium extension may exist.…”
Section: Discussionmentioning
confidence: 71%
“…Our observations are also consistent with the finding that the presence of a pterygium can be associated with deep corneal changes at the level of the endothelium and Descemet membrane and that endothelial cell density may be lower in these eyes. 47 Furthermore, limbal focusing may also affect corneal nerves as they cross the limbus, allowing the possibility of neuropeptide involvement in pterygium pathogenesis and explaining corneal sensory alterations in pterygium patients. 48 If corneal nerves are implicated, their radial distribution may also help to explain pterygium shape.…”
Section: Peripheral Light Focusing and Pterygium Pathogenesismentioning
confidence: 99%
“…13 Mootha et al demonstrated deep corneal marks at the level of the endothelium and descement membrane in patients with long-standing pterygium. 6 However, recently no investigators have reported the effects of the pterygium surgery on the anterior chamber parameters in addition to the changes in visual acuity and corneal topography.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The induction of astigmatism due to the invasion of the pterygium into the cornea has been reported by numerous studies. [6][7][8][9][10] The pterygia can decrease vision by occluding the visual axis or by inducing with-the-rule astigmatism with locally flattening the cornea. [6][7][8][9][10] In addition, pterygia can lead to the deterioration of the quality of visual performance by increasing the ocular wavefront aberrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation